‘The Sarmatian In Languages Trained’. Staniskaw Grzepski (1524-1570) As A Researcher Of The Hebrew Bible And The Septuagint - Linke, Waldemar (Studia Theologica Varsaviensia, 2019)
Stanisław Grzepski (1524-1570) an outstanding classic and biblical philologist, the first Greek permanent lecturer of this language at the Krakow Academy. He combined philological interests with the passion of numismatist-collector and researcher of biblical antiquities. The fruit of his erudite knowledge in this area was published in the printing house of Krzysztof Plantin in Antwerp in 1568, the work of De multiplici siclo et talento hebraico. The Cracow scholar in the subtitle referred to Guillaume’s Budé earlier work De asse et partibus eius. Despite the fact that Grzepski presents himself to the reader as the author of a summary of the extensive work of a French scholar and diplomat, he created a work independent and in many places polemic with the findings of the famous predecessor. The article shows the character and significance of the work of Stanisław Grzepski, which has become a part of European science for over 200 years as a textbook of numismatics and biblical archeology.